Exploring the Potential of Ramie Fiber Composites as Eco-friendly Materials for Medical Prostheses - Ramadhana Luhur Prabangkara; Sugeng Hadi Susilo (CV. Creative Tugu Pena, 2023)
The insect Callosobruchus maculatus, is responsible for serious damages in the storage of grains of diverse cultures, among them, the one of the beans. Therefore the development of substances capable of being an alternative to minimize agricultural losses and thus contribute to food security of the population is a current necessity.This research aims to explore new materials derived from natural fibers for the development of environmentally friendly and recyclable medical devices, particularly prostheses. The focus is on utilizing ramie fiber, a natural fiber, as a substitute for artificial fibers and plastics in composite materials. The study investigates the impact and bending strength of ramie fiber composites by varying the volume fraction and fiber orientation. The experimental design involves three volume fractions (1%, 3%, and 5%) and three fiber orientations (10°, 20°, and 30°). Hand lay-up method is employed on molds, ASTM D256 impact tests and ASTM D7264 bending tests are conducted to assess the mechanical properties. The findings indicate that the ramie fiber composite with a volume fraction of 5% and fiber orientation of 30° exhibits the highest bending strength, measuring 471.1 Mpa. Similarly, this composition demonstrates the highest impact strength value of 26,558,720 Pa. Overall, this research contributes to the advancement of sustainable materials for medical prostheses and highlights the significance of optimizing the composition of ramie fiber composites to enhance their mechanical properties. Keywords: Ramie Fiber, Composite Materials, Medical Prostheses